Kajian terhadap sistem pengurusan penyelenggaran Jabatan Perumahan dan Pembinaan Angkatan Tentera Malaysia - Jaafar, Abu Almohtar (2005)
Maintenance of assets particularly building is important as to maintain the high moral of the soldiers in order for them to achieve successfully the objectives and missions of the Ministry of Defence. Poorly maintained buildings will somehow tarnish the image of Malaysian Armed Forces (MAF). The MAF owned 182 camps with 33,000 buildings for the three services, Army, Navy and Air Force. Public Works Department (JKR) and Directorate of Accommodations and Works (A&W) which is under Malaysian Armed Forces maintained these buildings. The MAF received budgetary allocation from the Ministry of Defence annually and subsequently reallocate to JKR and A&W for execution of maintenance works. Recently, the maintenance works carried out were questionable as there were many complaints among the occupants. This study was carried out with aim to investigate and evaluate the management of maintenance system practised by MAF currently. Questionnaires was designed to evaluate the shortcoming of the ongoing system. A modal data flow diagram was developed to help in better understanding of the whole management system. The findings suggest that a proper building record should be built and an integrated maintenance management system to be developed. Thru this system it could enhance the overall maintenance management in giving quality services. Thus, thru sharing integrated maintenance management system repair and maintenance of other buildings components could be well planned and optimised the allocation given.